2013
DOI: 10.5021/ad.2013.25.4.428
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological Correlation in Post-Burn Hypertrophic Scar for Pain and Itching Sensation

Abstract: BackgroundHypertrophic scar following a burn is caused by the excessive deposit of collagen resulting in an exaggerated wound healing response. The burn patient complains of pain and itching over the scar, which can give rise to cosmetic and functional problems.ObjectiveThe aim of this study was to investigate the clinical and histological correlation of a hypertrophic burn scar for itching and pain sensations.MethodsThirty-eight patients underwent a scar release and skin graft. the modified Vancouver scar sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
3
27
0
1
Order By: Relevance
“…However, to date we have not found a publication comparing and measuring the epidermal thickness of sufficiently matured scars (≥ 1 year old) of the entire scar spectrum in a standardized, quantifiable manner. Hypertrophic scars also showed a trend towards increased epidermal thickness compared with normal skin and normotrophic scars, in line with Andriessen et al . However, in our study only keloid scars were found to have significantly increased epidermal thickness compared with normotrophic scars in addition to normal skin.…”
Section: Discussionsupporting
confidence: 92%
“…However, to date we have not found a publication comparing and measuring the epidermal thickness of sufficiently matured scars (≥ 1 year old) of the entire scar spectrum in a standardized, quantifiable manner. Hypertrophic scars also showed a trend towards increased epidermal thickness compared with normal skin and normotrophic scars, in line with Andriessen et al . However, in our study only keloid scars were found to have significantly increased epidermal thickness compared with normotrophic scars in addition to normal skin.…”
Section: Discussionsupporting
confidence: 92%
“…This corroborates outcomes showing that this neuropeptide is especially elevated in case of hypertrophic scars, a complication tightly correlated with thermal injury and highly associated with itching (158)(159)(160). All of these data support many neurophysiological studies demonstrating that itching results from neuropathic mechanisms (161).…”
Section: Itching and Paresthesiasupporting
confidence: 87%
“…This may be because pain level would decrease but itchiness would increase during the period from wound healing to 6 months after injury. Itching usually begins at the time of wound healing and peaks at approximately 3e12 months or later (Choi, Kim, Kim, Jang, & Kwak, 2013). Rehabilitation can help to ease the uncomfortable symptoms of itching, as confirmed in previous studies (Cho et al, 2014;Li-Tsang, Zheng, & Lau, 2010;Wiechman, 2011).…”
Section: Pain and Itchinessmentioning
confidence: 54%